(3JaSjQ GdbQBfs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf Hf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd efGXe cdGeg eXGgQ MSf UaGJg hWhGdY UaGJg eWGdY fhQ PGJg s
(3BNQgG (B:s
(3CeG ai ShQI GdgGOi Gfce cfJe JCJhf Yf Gdjejf hGddg GdYGeQ hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B438s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG RNGQa s
Keywords: (3GdJaSjQ hYdhe GdbQBfs